The effect of SBE on the properties of cement sand brick - Mohd Amirul Radzi, Mohd Radzami (2017)
Cement sand brick is a type of brick made from a mixture of cement and sand. The characteristics of sand are the main reason why it is in great demand in the construction industry. On the other hand, spent bleaching earth (SBE) is a solid waste from industrial sector mainly generated from the edible oil processing that is usually dumped at landfill. Surprisingly, the characteristics of both materials which are sand and SBE are almost identical. By replacing sand with SBE, sand mining and waste disposal problems can be reduced as well as economical cement sand brick can be produced. This study aims to investigate the effect of SBE as partial sand replacement on the properties of cement sand brick. The field of studies also covers important parameters including compressive strength, flexural strength, and water absorption in determining the engineering properties. The compressive, flexural and water absorption tests for these required parameters will be conducted on 7 and 28 days after the cement sand bricks undergo water curing. This study found that the samples with 20% SBE exhibited higher value of compressive and flexural strengths with the lowest moisture absorption compared to other samples.